Evolving funding strategies for research software: Insights from an international survey of research funders - Eric A. Jensen; Daniel S. Katz (PLoS ONE, 2025)
Contemporary research heavily depends on software. Research software, comprising source code, algorithms, scripts, computational workflows, and executables produced during or specifically for research, is crucial in advancing scholarly knowledge. However, this aspect of contemporary research can only thrive if research funders effectively support it. This survey study of international research funders addresses the research questions: 1) How do international funders currently support research software? 2) What challenges are funders aiming to tackle with their research software programs? 3) How successful do funders think their programs are? Survey results reveal a variegated funding landscape for research software, encompassing open-source projects, open-science tools, discipline-specific add-ons, infrastructure software, data science and AI tools, and general technology projects that include research software. Funders reported working to integrate research software into their formal definitions of research, codified in funding models and policies. Funders have been working to revise policies and adopt international frameworks such as ADORE.software to acknowledge research software’s role better. Respondents described innovative funding models designed to support research software more effectively than traditional research funding mechanisms. Supporting Research Software Engineers (RSEs) was another priority. Funding programs aimed to provide financial support, career development, and recognition for RSEs. Fostering collaboration between RSEs and other researchers was a less prevalent but noteworthy target for research funders. Promoting open-science principles and open source software development and maintenance was prioritized by research funders with targeted policies and programs. Overall, the reported initiatives aimed to ensure long-term research software accessibility, sustainability, and impact, with robust community engagement helping to contribute to a more effective research ecosystem. Finally, where funding programs for research software have been running for long enough to make an assessment, these efforts were overwhelmingly viewed as successful by the research funder representatives in our study.